Analisis Penggunaan Media Pembelajaran Microfost Teams Pada Mata Pelajaran IPS - Handaryani; Yudistia, Prabu Edo; Sartika, Eka (PT. LANCAR MEDIA KOMUNIKASI, 2023)
The aim of this research is to determine the effectiveness of useMicrosoft Teams in social science subjects. The research method used is descriptive qualitative using Miles and Huberman data analysis techniques which consist of data reduction, presentation and inference or verification. This research uses observation, interview and documentation guidelines. The results of this research show that the use of Microsoft Teams as a learning tool in social studies subjects is considered effective as reflected in learning effectiveness indicators which include teaching quality, appropriate level of teaching, incentives. and the time that must be shared together to express it. All aspects and performance indicators are continuous with each other and have met the performance declaration criteria.